Cracking due to alkali-silica reaction in slab at the Jaguari hydroelectric power plant - A qualitative studyes - Akasaki, Jorge Luís [UNESP] (2013)
The concrete structures of Jaguari Hydro Power Plant (HPP) display cracks due to the occurrence of Alkali-Silica Reaction (ASR). The qualitative analysis of the cracks that occur in the slab of the water intake structure was performed through in-loco visual mapping, and through results from the computational analysis, using the finite element method. The cracks were mapped using the plastic film technique with ink pens. The computational analysis was performed with a commercial program using bidimensional elastic elements, CSQ - Constant Strain Quad. The comparison of the results with the two techniques showed that the most intense cracking observed in certain regions of the slab coincides with the occurrence of the maximum tensions when an expansion in the walls of the intake is simulated, which can explain the origin of the cracks observed in the slab.